2016
DOI: 10.1186/s12913-016-1904-6
|View full text |Cite
|
Sign up to set email alerts
|

Methods used to address fidelity of receipt in health intervention research: a citation analysis and systematic review

Abstract: BackgroundThe American Behaviour Change Consortium (BCC) framework acknowledges patients as active participants and supports the need to investigate the fidelity with which they receive interventions, i.e. receipt. According to this framework, addressing receipt consists in using strategies to assess or enhance participants’ understanding and/or performance of intervention skills. This systematic review aims to establish the frequency with which receipt is addressed as defined in the BCC framework in health re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
104
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 102 publications
(602 reference statements)
1
104
0
Order By: Relevance
“…Intervention records (e.g., attendance or homework) were also used to measure engagement. Intervention records can be considered an objective measure of receipt (Gearing et al ., 2011; Rixon et al ., 2016) and participation (Saunders, Evans, & Joshi, 2005). However, these measures are limited by their inability to monitor how much participants understand and use the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intervention records (e.g., attendance or homework) were also used to measure engagement. Intervention records can be considered an objective measure of receipt (Gearing et al ., 2011; Rixon et al ., 2016) and participation (Saunders, Evans, & Joshi, 2005). However, these measures are limited by their inability to monitor how much participants understand and use the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This finding demonstrates that the reporting of psychometric qualities in the complex, face‐to‐face health behaviour change interventions included in this review, may not be as infrequent as previously suggested in different populations (Baer et al ., 2007; Breitenstein et al ., 2010; Maynard et al ., 2013; Rixon et al ., 2016). However, not all studies reported psychometric qualities, and fewer reported implementation qualities, despite the importance of psychometric and implementation qualities (Gearing et al ., 2011; Glasgow et al ., 2005; Holmbeck & Devine, 2009; Lohr, 2002; Stufflebeam, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audio-recording all sessions and using multiple researchers to reliably rate a percentage for fidelity is the current gold standard (Lorencatto et al, 2013). To measure engagement, self-report, attendance records, and multiple measures have been used (Gearing et al, 2011;Hankonen et al, 2015;Rixon et al, 2016;Walton et al, 2017). There is currently no consensus regarding the gold standard method to measure engagement in face-to-face interventions (Walton et al, 2017).…”
Section: Statement Of Contributionmentioning
confidence: 99%
“…There is currently no consensus regarding the gold standard method to measure engagement in face-to-face interventions (Walton et al, 2017). For example, receipt has been measured most commonly using quantitative measures (Rixon et al, 2016). For example, receipt has been measured most commonly using quantitative measures (Rixon et al, 2016).…”
Section: Statement Of Contributionmentioning
confidence: 99%